COVID-19 Pneumonia in Children: From Etiology to Management - Parisi, Giuseppe Fabio; Indolfi, Cristiana; Decimo, Fabio; Leonardi, Salvatore; Miraglia del Giudice, Michele (Frontiers in Pediatrics, 2020)
COVID-19 is less serious in children than in adults. However, respiratory management dominates the clinical picture of hospitalized COVID-19 even in children. In some case series, deterioration of the clinical picture wherein dyspnea, cyanosis, and the onset of acute respiratory distress syndrome (ARDS) emerged approximately 8–10 days after the onset of SARS-CoV-2 infection, which could rapidly progress to multiple organ failure and death. This review aimed to evaluate the characteristics of COVID-19 pneumonia in pediatric populations, beginning from its etiology and pathological mechanisms and closing with its clinical management.